COMMUNITY‐BASED WASTE MANAGEMENT - Kusumadinata, Ali Alamsyah (Universitas Djuanda, 2016)
Waste management is an absolute must do in micro aspects such as village, NeighborAssociation, Citizens Association, and the domestic sphere. This management should bemanaged based on collaboration between the government, public/corporate and private.Waste provide their own assessment among people hence the need for waste managementmodel that is based on existing communities in the village to the central location. This paperis a reflection of the waste collection movement activities conducted in February to April2015 in the village of Babakan. The findings of this paper is waste is something of value thatcan be converted into income communities if managed properly. Regulation in the wasteneeds to be a legal basses in building mutual awareness. Community participation isabsolutely the subject of the development of waste so that the model CBSWM (CommunityBased Solid Waste Management) could be run well.